Creutzfeldt-Jakob Disease as a Cause of Cognitive Decline and Seizures in the Elderly: Diagnostic Pointers and Strategy for Investigation - R. Williams; F. Cresswell; M. McClure; R. Lane (Case Reports in Medicine)
Cognitive decline affects one in twenty people over the age of 65. There is often a paucity of clues as to the underlying pathology, and while the diagnosis will usually prove to be either Alzheimer’s disease or vascular dementia, there may be clinical features suggesting rarer alternatives. This case of a 71-year-old lady with a 3-month history of progressive cognitive decline illustrates clinical features suggestive of Creutzfeltd-Jakob disease such as rapid decline in conscious level and myoclonic jerking. Diagnosis was confirmed by 3 means: (1) Electroencephalogram demonstrating periodic sharp wave complexes, (2) MRI brain showing cortical ribboning and high signal in the caudate nucleus, and (3) presence of protein S100 and protein14-3-3 in the cerebrospinal fluid. Postmortem brain histology confirmed a typical spongiform encephalopathy. Establishing an underlying aetiology is dementia is important not only for prognostic reasons but in order to detect potentially reversible causes. In cases of an atypical dementing illness our proposed investigations may assist in confirming or excluding underlying Creutzfeltd-Jakob disease.